Pembelajaran Menulis Karangan Berbasis Kearifan Lokal Bali pada Siswa Kelas V SD : Learning to Write Essays Based on Balinese Local Wisdom for Fifth Grade Elementary School Students - Maulida, Ikrima; Sidabutar, Gita Septianuli; Lestari, Eci Anita; Sari, Cut Kumala; Mulyahati, Bunga (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the implementation of Indonesian language and literature learning based on Balinese local wisdom in writing essays for fifth-grade students at SDN 7 Pemecutan. The study employed a qualitative descriptive approach, involving 31 students, a class teacher, and the principal as subjects. Data were collected through participatory observation, in-depth interviews, and documentation, and then analyzed using the Miles & Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results showed that learning began with the delivery of narrative essay writing material through presentation media, followed by an introduction to the values of Balinese local wisdom. Students were directed to identify, understand, and relate local cultural values ??to everyday experiences, then express them in the form of narrative essays. This process made students more interested, creative, and able to produce writing that is relevant to the cultural context. The teacher acted as an active facilitator, guiding students individually and in groups so they could develop ideas, text structure, and written expression. The evaluation results showed that more than half of the students achieved writing skills above the Minimum Competency (KKM), although some still struggled to express their ideas effectively. These findings confirm that integrating local wisdom not only enhances writing skills but also strengthens students' cultural identity and critical thinking. However, obstacles such as time constraints and conventional evaluation methods still need to be addressed. Therefore, this study recommends the development of more comprehensive evaluation strategies and the implementation of differentiated writing instruction to accommodate the diverse abilities of students.